How to catch a frog : - Ross, Heather (STC Craft, 2014)
Stories of growing up in rural Vermont as part of an eccentric family of artists and idealists, which involved self-imposed poverty, innovative living, daily lessons in self-reliance, and a deep appreciation for the natural beauty of the environment.